Application of the Quiz Team Method to Improve Learning Outcomes of Elementary School Students on the Material of Mutual Cooperation Lifestyle - Intaniasari, Yossinta; Subiyantoro, Singgih; Suparti, Suparti (Indonesian Journal of Instructional Media and Model, 2023)
The quality of learning strongly influences the success of education. Pancasila education is a crucial lesson taught in elementary schools because it directs the behavior and character of students so that it conforms to the norms, customs, and rules that apply. This study aims to improve the learning outcomes of fourth-grade students in the material of cooperation lifestyle by applying the Quiz Team learning method at Elementary School. This research uses classroom action research or PTK by applying the research design from Kemmis & Taggart covering four stages: planning, action, observation, and reflection. The research subjects were fourth-grade students at SD Negeri Godog 01, totaling 17 students. Data collection techniques through learning achievement tests, observations, and documentation. Data analysis was descriptive qualitative, and quantitative. The indicator of success is ?75% of the number of students who have exceeded the specified KKM. The results showed that the application of the Quiz team learning method to the Pancasila Education subject was able to improve the learning outcomes of fourth-grade students at SD Negeri Godog 01. Before being given action, the acquisition of student learning outcomes that exceeded the KKM was only 12 students or equivalent to 70.5%. In the action activities of the first cycle, students who exceeded the KKM were still the same as before, but there was an increase in the average class value of 78 to 82. In cycle II, as many as 15 (88.2%) exceeded the completeness score. The class average cycle I and II scores rose from 82 to 85. In conclusion, the quiz team method was effectively used to improve learning outcomes in the material of the cooperation lifestyle of elementary school students. Overall, this research contributes to improving learning outcomes that end at students' academic level.